Electrochemical Behavior of Quinoxalin-2-one Derivatives at Mercury Electrodes and Its Analytical Use - Milan Zimpl; Jana Skopalova; David Jirovsky; Petr Bartak; Tomas Navratil; Jana Sedonikova; Milan Kotoucek (The Scientific World Journal)
Derivatives of quinoxalin-2-one are interesting compounds with potential pharmacological activity. From this point of view, understanding of their electrochemical behavior is of great importance. In the present paper, a mechanism of electrochemical reduction of quinoxalin-2-one derivatives at mercury dropping electrode was proposed. Pyrazine ring was found to be the main electroactive center undergoing a pH-dependent two-electron reduction process. The molecule protonization of nitrogen in the position 4 precedes the electron acceptance forming a semiquinone radical intermediate which is relatively stable in acidic solutions. Its further reduction is manifested by separated current signal. A positive mesomeric effect of the nonprotonized amino group in the position 7 of the derivative III accelerates the semiquinone reduction yielding a single current wave. The suggested reaction mechanism was verified by means of direct current polarography, differential pulse, cyclic and elimination voltammetry, and coulometry with subsequent GC/MS analysis. The understanding of the mechanism was applied in developing of analytical method for the determination of the studied compounds.